International Collaboration on Palliative Care Development Between ASCO and the Land of Hornbills - Yin, Yee Wong; Aaron Zi, Jian Chiew; Vanessa, Eaton; Frank D., Ferris; Megan, Kremzier; Boon, Leong Lim; Winnie Hui, Yee Ling; Asri, Said; Vanessa, Sarchet; Tung, Hui Tiong; Pei, Jye Voon; Yoke, Ling Choo (American Society of Clinical Oncology, 2023)
PURPOSE Palliative care in Sarawak is mainly provided by health care professionals with limited formal training in palliative care. Therefore, in 2020, collaborative work between Sarawak General Hospital, University Malaysia Sarawak, and ASCO began. This study reports on the outcome of this collaboration. METHODS The collaboration was initiated with the first ASCO Palliative Care e-course, Train the Trainer program, International Development and Education Award—Palliative Care and translation of ASCO Palliative Care Interdisciplinary Curriculum resources. RESULTS This collaboration has resulted in the change of practice of palliative care among the oncology team of Sarawak General Hospital. CONCLUSION It encourages more timely palliative care referrals to ensure that patients with complex physical, psychosocial, and spiritual needs have the necessary input and support from the palliative care team throughout the course of patients’ illnesses.